TDD AS A METHODOLOGY IN SOFTWARE DEVELOPMENT - Ferreira, David Chaves; Pinto, Giuliano Scombatti (Revista Interface Tecnológica, 2022)
As software development increases, so does its complexity. The number of bugs might also increase, so there is a need of testing it to validate the system functionality. Such tests provide the developer safety while implementing security as codes, so there will be no new bugs in the end. Furthermore, when something new is implemented in the system, a test is created to ensure that the new functionality works, not affecting the existing ones. Besides that, tests also have the role of recording data for those ones that already read codes. That said, the more tests, the easier it will be to maintain them. However, creating tests is not as simple as it seems, given that if someone does not use a proper methodology, things might get more complicated than necessary. Finally, this research aims at showing how to make the most of tests by using the TDD methodology, as well as how it works in creating codes. In the end of this paper, we expect that our reader gets more acquainted on how he or she might start creating codes using the methodology aforementioned and how to get positive results on software development.
Keywords: Tests; TDD; TDD Methodology